Poverty as Disembodiment: The Enfreakment of Animalized Philippine Bodies in Malou Jacob’s “ Juan Tamban ” and Nick Pichay’s “ Babaeng Tilapia, Natagpuan sa Coastal Road” - Ancheta, Maria Rhodora G. (Philippine Humanities Review; Vol 19 No 2 (2017), 2019)
This paper, in studying Malou Jacob’s now-iconic stage play “Juan Tamban” and Nicolas Pichay’s “Babaeng Tilapia, Natagpuan sa Coastal Road”, a teleplay, seeks to read the presentation of animalized bodies of the poor in the Philippines as tropes of freakery and grotesqueness that perform/shape dis-embodiment. This animalization will indeed be examined as a project of dehumanization and as a campaign to mine both empathetic and antipathetic responses to poverty in Philippine life. However, in tracking the incongruities of animalized, grotesque bodies in Jacob’s and Pichay’s plays, I posit that depictions of abjection in Philippine plays should not only be seen as mirroring real life poverty in the Philippines, but, as seen in these two “poverty plays”, animalization can also be examined as tactics that explore the dynamics and the plasticities of vulnerability, civilization, and mortality within the play as microuniverse, and within the world of the intended or the idealized audience. KEYWORDS: animalization, freakery, grotesque bodies, disability, normalcy